Global Transcriptomic Analysis of Inbred Lines Reveal Candidate Genes for Response to Maize Lethal Necrosis - Ann Murithi; Gayathri Panangipalli; Zhengyu Wen; Michael S. Olsen; Thomas Lübberstedt; Kanwarpal S. Dhugga; Mark Jung (Plants)
Maize lethal necrosis (MLN) is a significant threat to food security in Sub-Saharan Africa (SSA), with limited commercial inbred lines displaying tolerance. This study analyzed the transcriptomes of four commercially used maize inbred lines and a non-adapted inbred line, all with varying response levels to MLN. RNA-Seq revealed differentially expressed genes in response to infection by maize chlorotic mottle virus (MCMV) and sugarcane mosaic virus (SCMV), the causative agents of MLN. Key findings included the identification of components of the plant innate immune system, such as differentially regulated R genes (mainly LRRs), and activation/deactivation of virus resistance pathways, including RNA interference (RNAi) via Argonaute (AGO), Dicer-like proteins, and the ubiquitin–proteasome system (UPS) via RING/U-box and ubiquitin ligases. Genes associated with redox signaling, WRKY transcription factors, and cell modification were also differentially expressed. Additionally, the expression of translation initiation and elongation factors, eIF4E and eIF4G, correlated with the presence of MLN viruses. These findings provide valuable insights into the molecular mechanisms of MLN resistance and highlight potential gene candidates for engineering or selecting MLN-resistant maize germplasm for SSA.